Customer service personnel’s perceptions of customers: The case of a telecommunications firm - Ernest Cyril, de Run; Thang, Florence Chin-Yin (Universiti Malaysia Sarawak, (UNIMAS), 2007)
This paper sets out to extend current knowledge on perception of customer service personnel (CSP) towards customers. It examines these perceptions by employing the CAB Paradigm, utilizing an interview followed by questionnaires based on the interview findings for CSPs in a telecommunications firm in Malaysia. Data collected from the interview was analyzed using frequency distribution and data from the questionnaire was analyzed using factor analysis. Findings indicated the most identified variable was “Interested” and the least was “Gross/Unpleasant”. Factor analysis indicated 9 views of customers termed as Mr. Hot, Mr. Mix Up, Mr. Pushy, Mr. Slow, Mr. Serious, Mr. Professional, Mr. Simple and Mr. Cheerful. The number of respondents and the subsequent weak KMO limit the study. Nevertheless, it provides a basis for the CAB Paradigm to explain why customer service in Sarawak is weak. The implications of the study to management and HRM department are strong as they indicate that CSP’s views of customers are negative, and such personnel thus require further training and supervision on how to treat customers. It is rare to find articles that look at CSP’s view of customers, as the literature is chock-a-block with the views of customers. This study allows for a preview into the mind of CSPs.